PENYELESAIAN PELANGGARAN PEMILU TAHUN 2014 DAN PEMILU KEPALA DAERAH DAN WAKIL KEPALA DAERAH TAHUN 2015 DI JAWA TENGAH - Nawangsih Sekarwidhi; Nur Hidayat Sardini; Fitriyah - -; Nenny Marlina (Journal of Politic and Government Studies, 2018)
This study aims to determine the mode of violation, the factors that cause some cases are not followed up and issues handling violations that occurred in the 2014 General Election and Regional Head Election Year 2015 in Central Java. Type of research used in this research is case study research type through qualitative approach. Sources of data used in the form of primary data derived from the results of in-depth interviews of some research informants and secondary data in the form of archives and documentation. The technique of selecting informants using purposive sampling. The results of this study found that the violation modes that occurred were violations of electoral administration, violations of election criminal conduct, violation of the code of conduct of election organizers, and there were disputes between Pemilu and PHPU. Furthermore, in the case of the handling of election violation, the Election Supervisory Board still encounters several problems, namely: Insufficient Human Resources, Witness, Terpaor, and Uncooperative Reporter, limited handling time, Uncertain Evidence, and there is a difference of perspective between Institutions. Factors that cause some cases to be discontinued are: Evidence is difficult to find, limited handling time and Witness, Terpaor, and Uncooperative Reporting. The recommendation that the authors give is for the implementation of duties and authority of the Election Supervisory line from the bottom level is given optimal technical training so that in the handling of a case can be maximized. It is recommended that the recruitment of Human Resources in the Election Supervisory Majority having prior legal background or having election knowledge as well as regulations related to violations in the General Election needs to accommodate strict sanctions for violators in order to create a deterrent effect for them and fear for others to commit violations . Keywords: Election Violation Mode, Handling Issues, Cause Factor Case terminated